Bulk texture evolution of nanolamellar Zr–Nb composites processed via accumulative roll bonding. (15th June 2015) - Carpenter, J.S.; Nizolek, T.; McCabe, R.J.; Knezevic, M.; Zheng, S.J.; Eftink, B.P.; Scott, J.E.; Vogel, S.C.; Pollock, T.M.; Mara, N.A.; Beyerlein, I.J.
Abstract: It was recently demonstrated that bulk two-phase 50/50 Zr–Nb nanolayered composites with 90 nm individual layers can be fabricated from an initial coarse-layered composite with 1 mm layers via the severe plastic deformation process of accumulative roll bonding. During the deformation, the Zr phase retained its hcp crystal structure and the Zr–Nb interface remained sharp. Here we use a combination of neutron diffraction and dislocation-based polycrystal plasticity constitutive modeling to assess the evolution of texture and deformation mechanisms over a four order-of-magnitude range in layer thickness. The phase textures in the nanocomposite strongly deviate from that of Zr or Nb rolled in monolithic form, becoming highly peaked and intense. The model suggests that texture development in the Nb phase is associated with multiple slip and contributions from both 1 1 2〈1 1 0〉 slip and 1 1 0〈1 1 0〉 slip. In the Zr phase the model suggests that the texture develops due to a predominance of prismatic 〈a〉 and basal 〈a〉 slip.